P108 Omalizumab for severe allergic asthma: cost-effective or priceless?. (2nd December 2011) - Miles, J; Green, D
Abstract : Background: Omalizumab is licensed for the treatment of severe allergic asthma to help reduce severe exacerbations. However the decision as to whether to consider Omalizumab therapy is based on a 16 week assessment period with no reference to the licensed indication at all! We were therefore keen to examine omalizumab efficacy in terms of exacerbation reduction in our severe asthma clinic. Methods: 40 patients had received omalizumab treatment for at least 12 months, on the basis of a successful 16 week assessment period. Hospital and GP records were scrutinised to assess exacerbation frequency and unscheduled hospital attendance before and after treatment. Costs for asthma admissions, attendance for clinic and price per omalizumab vial were analysed. In addition a repeat patient survey was undertaken to assess satisfaction with therapy and our service using a previously validated tool.1 Results: Complete data was available for 20 patients. A sequential eduction in unscheduled hospital; contacts was seen throughout the first year following commencement of omalizumab. Average cost savings on unscheduled hospital attendances were £2500 per annum. Average costs of attendance for injections were £2080 per annum. Treatment costs varied between £3250 and £26 000 per patient per annum. We did not have data on the absenteeism rates from those patients currently in full or part time employment. Patient satisfaction with both Omalizumab and the clinic set up remained high as in keeping with our previous assessment. Conclusions: Omalizumab does reduce exacerbation frequency in patients with severe allergic asthma. Patients are extremely satisfied with the efficacy of therapy. The costs of reduced unscheduled care offset the costs of extra planned attendances for injections. Although an expensive treatment, there may be many potentially hidden physical, social and economic benefits of omalizumab therapy. Sophisticated health economic analysis is required to pursue this hypothesis.